1997
DOI: 10.1038/bjc.1997.291
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of bladder cancer associated with chronic exposure to arsenic

Abstract: Summary A high incidence of bladder cancer has been documented in an area of chronic arsenic (As) exposure. This study investigates the characteristics of As-associated (n = 49) and other (n = 64) bladder cancers. A higher histological grading was observed for the As-exposed tumours (P = 0.04), but no other difference in pathobiological features or prognosis was found between the two groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Guo et al (2001a) reported significantly increased rate differences for bladder cancer in men and women in Taiwan exposed to 0.64 mg arsenic/L in the drinking water, but not at lower exposure levels. The arsenic-induced bladder tumors do not appear to be histologically different than similar bladder tumor types of nonarsenic origin (Chow et al 1997), although they tended to be more pronounced. In contrast, Michaud et al (2004) reported no correlation between arsenic levels in toenails and the incidence of bladder cancers in Finnish workers.…”
Section: Health Effectsmentioning
confidence: 59%
“…Guo et al (2001a) reported significantly increased rate differences for bladder cancer in men and women in Taiwan exposed to 0.64 mg arsenic/L in the drinking water, but not at lower exposure levels. The arsenic-induced bladder tumors do not appear to be histologically different than similar bladder tumor types of nonarsenic origin (Chow et al 1997), although they tended to be more pronounced. In contrast, Michaud et al (2004) reported no correlation between arsenic levels in toenails and the incidence of bladder cancers in Finnish workers.…”
Section: Health Effectsmentioning
confidence: 59%
“…31 The findings that urothelial carcinoma from BFD area has a higher rate of DNA aneuploidy, 9 histological anaplasia, 10 and unusual p53 mutational spectra 11 appear to support the promoter role of arsenic in the development of urinary tract carcinoma, although the molecular mechanisms underlying the pathogenesis of human cancer remain to be elucidated.…”
Section: Discussionmentioning
confidence: 90%
“…First, our prior cohort study found that bladder cancer from the BFD-endemic area had a significantly higher incidence of histological anaplasia, especially bizarre giant cells, compared with nonendemic controls. 10 Second, the clear cell differentiation was suggested to be one of the early histological changes of malignant transformation of the liver. 16 …”
Section: Study Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistopathological studies showed that arsenic-induced bladder tumors were pathobiologically and prognostically identical to non-arsenical bladder tumors (143). At the cytological level, it was found that level of arsenic exposure was directly correlated with the induction of chromosomal instability and that tumors from arsenic exposed individuals might behave much more aggressively than bladder tumors of non-exposed individuals (144,145).…”
Section: Arsenic-induced Non-dermatological Cancersmentioning
confidence: 99%